Mobile robot for surveillance - Cham, Alan Toshihito Jun Wei (2010)
Robots have been used widely to take over human’s jobs extensively nowadays. There are some jobs with high risks and require long working hours. It would be too risky to put people in those jobs and thus robots are implemented to take over those jobs for people. A mobile robot for surveillance will be revived, modified and developed to ease the job of people for surveillance and to improve overall work efficiency.